Efficacy of imidacloprid, a new insecticide for controlling Myzus nicotianae on flue cured virginia tobacco (Nicotiana tabacum) - RAMAPRASAD, G; SRIDHEER, U; SITARAMAIAH, S; RAO, S NAGESWARA; SATYANARAYANA, V V (The Indian Journal of Agricultural Sciences, 2013)
A field experiment was conducted during 1991-94 to evaluate the performance of a new insecticide imidacloprid and other insecticides for controlling tobacco aphid (Myzus nicotianae Blackman) on flue cured virginia tobacco (Nicotiana tabacum L.). Both the formulations of imidacloprid (70 water soluble powder) and 200 soluble concentrates/litre at 50 g ai or acephate 750 g ai/ha as 2 foliar sprays or combination of imidadoprid 70 water soluble powder at 100 g ai/ha as plant hole treatment + 1 foliar spray ofimidacloprid 200 soluble concentrates/litre at 50 g ai/ha effectively controlled the aphids throughout the season and recorded better yield of cured leaf, bright-leaf and grade index. Oxydemeton methyl 0.05% foliar spray controlled the aphid effectively only up to 8 days after spray.